PENGARUH KONTEN MARKETING DAN MARKETPLACE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (STUDI KASUS TOKO BATIK DEANDRA) - Surya R, Adi; Yopita, Yopita (STMIK Pringsewu, 2025)
The advancement of digital technology has encouraged businesses, especially micro, small, and medium enterprises (MSMEs), to utilize content marketing and marketplace platforms to reach a wider consumer base. This study aims to analyze the influence of content marketing and marketplaces on consumer purchasing decisions, with a case study on Batik Deandra, an MSME actively engaged in digital marketing. The research adopts a quantitative approach using a questionnaire distributed to 100 respondents. Data were analyzed using multiple linear regression. The results indicate that both content marketing and marketplace presence have a significant and positive influence-both simultaneously and partially-on consumer purchasing decisions. These findings highlight the strategic importance of quality content and optimized use of marketplace features in enhancing consumer engagement and purchase conversion, particularly in the MSME sector.